Case Report: Ménière's Disease-Like Symptoms in 22q11.2 Deletion Syndrome - Kwang-Dong Choi; Jeong-Yeon Kim; Seo-Young Choi; Eun Hye Oh; Hyun-Min Lee; Jieun Roh; Jae-Hwan Choi (Frontiers in Neurology, 2021)
The 22q11.2 deletion syndrome (22q11.2DS), caused by a microdeletion on the long arm of chromosome 22, is characterized by congenital heart disease, hypoparathyroidism, immunodeficiency, developmental delay, and velopharyngeal insufficiency. Anatomic malformations of the middle and inner ears are frequently present, leading to high prevalence of hearing impairment. We present a first case of 22q11.2DS showing fluctuating hearing loss with recurrent vertigo attacks, resembling Ménière's disease. A 38-year-old male known to have 22q11.2DS developed recurrent vertigo, tinnitus, and fluctuating hearing loss in the left ear during a 10-year follow-up period. During vertigo attack, he had spontaneous left-beating nystagmus with downbeat components, but bithermal caloric and video head impulse tests showed normal vestibulo-ocular reflex functions. Sequential pure tone audiograms demonstrated fluctuating sensorineural hearing loss (SNHL) in both ears, which finally progressed to permanent hearing loss in the left ear. Computed tomography imaging of the temporal bone exhibited bilaterally malformed lateral semicircular canals, and delayed 3D-FLAIR sequences revealed cochlear endolymphatic hydrops with dilation of the scala media in the left ear. This case shows that acute vertigo with SNHL can be one of the audiovestibular presentations in 22q11.2DS caused by disturbance of endolymphatic flow.